Comparison of financial performance and corporate social responsibility disclosures in Indonesian telecommunication companies before and during the Covid-19 pandemic (Asian Journal of Economics and Business Management, 2023)
This study compares the financial performance and corporate social responsibility disclosure in Indonesian telecommunications companies listed on the Indonesia Stock Exchange in 2018-2021 before and during the Covid-19 pandemic. This study used purposive sampling; namely, 18 companies were found to be eligible as samples. The data used in this study is secondary data taken from the official website of the Indonesia Stock Exchange. The analysis technique used is descriptive statistics, normality test, and different test (paired sample t-test). The study results show differences in the return on equity, current ratio, and debt to equity ratio before the co-19 pandemic and during the co-19 pandemic. Meanwhile, corporate social responsibility did not differ before the COVID-19 pandemic and during the COVID-19 pandemic.